Optimalisasi Kreativitas Siswa melalui Pelatihan Canva : Pengabdian kepada Siswa Kelas XII IPA di Madrasah Aliyah Muhammadiyah Pekanbaru - Resi Fazri Alfala; Neng Sholihat; Ahmadi Ahmadi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The development of information and communication technology has brought significant changes in the world of education, encouraging educational institutions to adopt more innovative and relevant learning methods. This article discusses the implementation of Canva graphic design application training at Madrasah Aliyah Muhammadiyah Pekanbaru, which aims to improve the creativity and digital skills of grade XII IPA students. This activity was carried out through an interactive theoretical and practical approach, allowing students to not only learn about graphic design, but also apply that knowledge in real projects. The results of the training showed high enthusiasm from students, as well as significant improvements in their technical abilities and creativity. Evaluation of student design work indicated that the hands-on learning method was effective in improving digital literacy. These findings provide important insights into the potential of technology in creating a dynamic and innovative learning environment, and can be a reference for other community service programs aimed at improving digital competence in education.